The Nature of Irrevocability: Anthropocene Nostalgia in Hayley Eichenbaum’s Photography Series The Mother Road - Relidzyńska, Alicja (Text Matters: A Journal of Literature, Theory and Culture, 2022)
The recent acknowledgement of the Anthropocene, resulting from the increasingly visible human-induced effects on the biosphere, has ultimately obliterated the nature/culture division (Latour; Chakrabarty), prompting sociocultural changes (Autin). Hayley Eichenbaum’s photography series The Mother Road (2015–19) serves as a prominent example of a contemporary American cultural text which reinterprets existing aesthetic strategies and shows symptoms of what I propose to identify as Anthropocene nostalgia. This new sentiment is characterized by the awareness that a return to the past is impossible and would be pernicious, given the detrimental effects of reckless capitalism fuelled by twentieth-century American consumer culture. This article aims to analyze this distinctive type of nostalgia and its juxtaposition with the Anthropocene in Eichenbaum’s series. An analysis of The Mother Road identifies why and how this new sentiment corresponds with the aesthetics of previous decades, as well as notions of temporality and time. Building on previously conceptualized traditions as codes of reference, Eichenbaum reinterprets the representation of Route 66 by playing with its iconography, creating images which evoke desolate, quasi-post-apocalyptic landscapes. With the use of synthetic colours, digital manipulation, kitsch imagery, and mindful deconstruction of past aesthetic strategies, the analyzed series demythologizes the past and displays the loss of both nature itself and of pre-Anthropocene perception.